Antigen-Specificity in the Thymic Development and Peripheral Activity of CD4+FOXP3+ T Regulatory Cells - Pohar, Jelka; Simon, Quentin; Fillatreau, Simon (Frontiers in Immunology, 2018)
CD4+Foxp3+ T regulatory cells (Treg) are essential for the life of the organism, in particular because they protect the host against its own autoaggressive CD4+Foxp3− T lymphocytes (Tconv). Treg distinctively suppress autoaggressive immunity while permitting efficient defense against infectious diseases. This split effect indicates that Treg activity is controlled in an antigen-specific manner. This specificity is achieved first by the formation of the Treg repertoire during their development, and second by their activation in the periphery. This review presents novel information on the antigen-specificity of Treg development in the thymus, and Treg function in the periphery. These aspects have so far remained imprecisely understood due to the lack of knowledge of the actual antigens recognized by Treg during the different steps of their life, so that most previous studies have been performed using artificial antigens. However, recent studies identified some antigens mediating the positive selection of autoreactive Treg in the thymus, and the function of Treg in the periphery in autoimmune and allergic disorders. These investigations emphasized the remarkable specificity of Treg development and function. Indeed, the development of autoreactive Treg in the thymus was found to be mediated by single autoantigens, so that the absence of one antigen led to a dramatic loss of Treg reacting toward that antigen. The specificity of Treg development is important because the constitution of the Treg repertoire, and especially the presence of holes in this repertoire, was found to crucially influence human immunopathology. Indeed, it was found that the development of human immunopathology was permitted by the lack of Treg against the antigens driving the autoimmune or allergic T cell responses rather than by the impairment of Treg activation or function. The specificity of Treg suppression in the periphery is therefore intimately associated with the mechanisms shaping the formation of the Treg repertoire during their development. This novel information refines significantly our understanding of the antigen-specificity of Treg protective function, which is required to envision how these cells distinctively regulate unwanted immune responses as well as for the development of appropriate approaches to optimally harness them therapeutically in autoimmune, malignant, and infectious diseases.